Enhancing bio-char calorific value through catalytic pyrolysis: The role of magnesium oxide-zeolite based catalysts - Alien Abi Bianasari; Saifullah Abu Bakar; Md Sarowar Khaled; Saepurahman Saepurahman; Dieni Mansur; Abul Kalam Azad (Center of Biomass & Renewable Energy (CBIORE), 2026)
The current research aims to improve the generation of bio-char with elevated higher heating values (HHVs) by utilizing magnesium oxide-zeolite-based catalysts across various temperature conditions. The exploration of biomass catalytic pyrolysis has intensified in the pursuit of sustainable energy solutions. Catalytic pyrolysis offers a technique to convert abundant and renewable biomass resources into valuable biofuels and bio-char, thereby improving energy security and reducing dependence on fossil fuels. The use of suitable catalysts in biomass catalytic pyrolysis is crucial for enhancing the yield of bio-char with higher calorific value. This investigation explores the impact of magnesium oxide-zeolite-based catalysts on the higher heating values of bio-char generated from coconut shells. The initial findings indicate a notable enhancement in the calorific value of bio-char. The HHV increased from 12.03 MJ/kg for untreated coconut shells to 20.06 MJ/kg with ZSM-5, ultimately reaching an impressive 38.11 MJ/kg with the MgO/ZSM-5 catalyst. The results demonstrate that the addition of magnesium oxide significantly improves the energy content of bio-char. Various combinations of magnesium oxide, such as MgO/ZSM-5, MgO/Y2O3/ZSM-5, and MgO/Mn3O4/ZSM-5, are evaluated for their effects on the pyrolysis process. The results demonstrate that the impregnation of metal oxides into zeolite catalysts enhances catalytic performance and facilitates the efficient conversion of coconut shells into high-energy bio-char. The findings highlight the promise of metal oxide-zeolite catalysts in improving bio-char quality and promoting the development of sustainable energy technologies.